Psoriasis as a psychodermatology disease - Bogdan Zrnić; Snežana Medenica; Aleksandra Salamadić; Zoran Pantić; Siniša Ristić (Биомедицинска истраживања, 2010)
Skin lesions have a strong influence on the mental health. Literature indicates the complex interrelationships between psychosocial factors and psoriasis, which substantially reduce the quality of life of these patients. These interrelationships are based on numerous interactions that exist between the immune, nervous and endocrine systems and they are the basis of interactions that exist between mental and somatic health and the environment. Psychodermatology was developed as a new interdisciplinary field, a connection between psychiatry and dermatology. More than just cosmetic disfigurement, psoriasis is associated with various psychopathological problems that may have an impact on patients, their families and society. Numerous psychological disturbances occur in patients with psoriasis. Also, a significant psychiatric comorbidity was found in patients with psoriasis. Exacerbation of psoriasis leads to a deterioration of mental health. The treatment of psoriasis requires an interdisciplinary approach of a dermatologist and a psychiatrist. Various forms of psychological interventions have been proposed as a potentially useful addition to a standard pharmacological treatment of psoriasis.
Keywords: psoriasis; stress; psychotherapy; immunoneuroendocrine interactions